1982
DOI: 10.1007/bf00242486
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity, storage, and aging: physiologic autoantibodies to cell membrane and serum proteins and the senescent cell antigen

Abstract: Normal human serum contains autoantibodies to a wide range of cellular and serum proteins. IgG autoantibodies to cell membrane proteins spectrin, syndein (Band 2.1), Band 3 degradation products, and the senescent cell antigen are among them. Physiologic autoantibodies to the senescent cell antigen, a approximately 62 000 dalton glycopeptide derived from Band 3, initiate removal of senescent, damaged, and stored cells in vivo. The senescent cell antigen is one of the two Band 3 degradation products (Mr approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
50
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 84 publications
2
50
0
Order By: Relevance
“…However, they do not agree on the molecular changes responsible for generating the antigen. Our evidence suggests that senescent-cell antigen is derived from band 3, probably by degradation (10,(25)(26)(27)(28)(29)(30)(31); Lutz and his colleagues have suggested that senescent-cell antigen is a dimer ofband 3 (32); Sayare et al (33) have shown that band 3 can cross-link with hemoglobin under oxidative conditions; and Low et al (34) have presented evidence that clustered band 3 can generate senescent-cell antigen. These membrane events are not mutually exclusive.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…However, they do not agree on the molecular changes responsible for generating the antigen. Our evidence suggests that senescent-cell antigen is derived from band 3, probably by degradation (10,(25)(26)(27)(28)(29)(30)(31); Lutz and his colleagues have suggested that senescent-cell antigen is a dimer ofband 3 (32); Sayare et al (33) have shown that band 3 can cross-link with hemoglobin under oxidative conditions; and Low et al (34) have presented evidence that clustered band 3 can generate senescent-cell antigen. These membrane events are not mutually exclusive.…”
mentioning
confidence: 65%
“…One hypothesis for the removal of senescent erythrocytes is that a "neo-antigen" appears on the surface of senescent cells leading to IgG binding and cellular removal (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). The "neo-antigen" is recognized by the antigen binding, Fab, region (3,10,11) of a specific IgG autoantibody in serum that attaches to it and initiates the removal of cells by macrophages (1)(2)(3)(4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymatic fragments of erythrocytes were generated by standard methods (4,13,14). Rabbit antibody to band 3 and antibody 980, a rabbit antibody to aged band 3 (precursor to senescent cell antigen), were prepared as described (15)(16)(17). Monoclonal antibodies were a gift from Michael Jennings (University of Texas at Galveston).…”
mentioning
confidence: 99%